O múltiplo em publicações de artistas : Rohnelt, Catanni e Mutran - Salvatori, Maristela (2019)
This article focuses on the artist’s book presenting different approaches of three contemporary artists based in southern Brazil: Mario Röhnelt, Maria Lucia Cattani e Flavya Mutran. Each one creates in their own way a multiple as an artist book